Life Satisfaction and Sense of Coherence of Breast Cancer Survivors Compared to Women with Mental Depression, Arterial Hypertension and Healthy Controls - Minna Salakari; Sakari Suominen; Raija Nurminen; Lauri Sillanmäki; Liisa Pylkkänen; Päivi Rautava; Markku Koskenvuo (My University, 2022)
The purpose of the study was to compare the life satisfaction (LS) and sense of coherence (SOC) of women recovering from breast cancer (BC) to LS and SOC of women with depression or hypertension and of healthy controls. Finnish Health and Social Support (HeSSup) follow-up survey data in 2003 was linked with national health registries. BC patients were followed up for mortality until the end of 2012. The statistical computations were carried out with SAS®. There were no significant differences in LS and SOC between the groups with BC, arterial hypertension or healthy controls. Women recovering from BC are as satisfied with their life as healthy controls, and their perceived LS is better and SOC is stronger compared to women with depression. SOC correlated positively (r2 = 0.36, p < 0.001) with LS. However, more studies on determinants of the LS are needed for designing and organizing health care services for BC survivors.
Building Sustainable Health Ecosystems